Estimasi Simpanan Karbon di Padang Lamun di Perairan Sumberkima Buleleng, Bali - Gilang Pratama; I Wayan Gede Astawa Karang; I Nyoman Giri Putra (Journal of Marine Research and Technology, 2023)
Seagrass is one of the vegetation that has the potential to absorb carbon in Sumberkima waters, Bali. This study aimed to determine the density of seagrass and the estimated value of carbon storage at the top of the substrate (leaves) and at the bottom of the substrate (roots and rhizomes) in Sumberkima waters, Bali. This research was conducted on two islands, namely Pulau Gisik and Pulau Pasir Putih, on September 11 to October 8, 2021, where each island was taken 5 stations with a quadrant transect size of 50cm x 50cm, where each line transect was taken seagrass every 0 m, 50 m, and 100 m. The types of seagrasses found on Pasir Putih Island were Thalassia hemprichii, Cyomodocea serrulata, and C. rotundata while on Gisik Island, the types of seagrasses found were Thalassia hemprichii, Enhalus acoroides, Cymodocea rotundata, C. serrulata, and Halophila ovalis. The density of seagrass on Pasir Putih Island was, on average, between 40 - 87 stands/m2 with the category of rare to somewhat dense, while on Gisik Island, the average is between 35 - 44 stands/m2, indicating a rare category. Estimated total carbon storage in the upper substrate (leaves) on Pasir Putih Island and Gisik Island. The value of carbon storage in Pasir Putih Island at the top of the substrate (leaves) was 0.04 tons/ha, while at the bottom of the substrate (rhizomes and roots) was 0.05 tons/ha, and the value of carbon storage in Gisik Island was at the top. the substrate (leaves) was 0.03 tons/ha, while at the bottom of the substrate (rhizomes and roots), it was 0.04 tons/ha